The clinical characteristics of older people with chronic multiple-site joint pains and their utilisation of therapeutic interventions: data from a prospective cohort study. Issue 1 (December 2016) - Raja, Rafi; Dube, Bright; Hensor, Elizabeth; Hogg, Sarah; Conaghan, Philip; Kingsbury, Sarah
Abstract Background Chronic multiple-site joint pain (MSJP) is common in older people and associated with poor outcomes, yet under-researched. Our aim was to detail the clinical characteristics of people with MSJP and their utilisation of therapies. Methods MSJP was defined as pain in at least one large joint and one other joint for >6 weeks in the last three months. A mixed community, primary and secondary care cohort of people >50 years old underwent detailed history and examination by a single clinician. Treatment utilisation was recorded comprehensively. Results 201 adults were recruited, 82 % women, mean age 63, BMI 31 kg/m2 . Median number of painful joints per patient was 6 (IQR 4–9; range 2–17); most common painful sites were knee (84 %), lower back (62 %) and shoulder (47 %). 194/201 (96 %) had an osteoarthritis (OA) diagnosis, 155/194 (80 %) also had soft tissue pathology and 72 % had back problems. 85 % had OA at multiple sites. Upper and lower limb weakness was common (90 and 77 % respectively). Lower limb weakness was significantly associated with obesity. Only 26 % had received written information about their joints. Though 79 % had attended physiotherapy, the majority (93 %) had muscle weakness. Only 36 % of overweight participants had accessed weight-loss support. Half of those with foot pain had seen a podiatrist or used appliances. Multiple concurrent pharmacological therapies were used by 47 %. Conclusion MSJP represents a combination of OA, back pain and soft tissue disorders; muscle weakness is extremely common. Therapies appear underutilised in people with MJSP. Identifying the reasons for this should guide effective intervention research.